Hubungan Beban Kerja Perawat Instalasi Gawat Darurat Dengan Kepatuhan Pelaksaan Standar Prosedur Operasional Penerimaan Pasien Baru di RSU GMIM Pancaran Kasih Kota Manado - Rahmawati Inggrit Yunus; Silvia Dewi Mayasari Riu; Irma M. Yahya (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Workload is a description of the volume of work. In hospitals, the workload covers many aspects and this has an impact on compliance with the implementation of SOPs for new patient admissions which can be influenced by high workloads. The aim of this research is to determine "The relationship between emergency room nurse workload and compliance with standard operational procedures for accepting new patients." This research was conducted using a cross-sectional Descriptive Analytical research method, which emphasizes the time of measurement or observation and independent and dependent variables only once. The population in this study was 23 subjekts with a sampling technique using total sampling technique and the sample for this study was 23 subjekts. Data collection uses questionnaires and observation sheets. Analyzed using the chi square test. Based on the chi-square results, it can be seen that the p value is 0.026, which is smaller than p (α < 0.5), so it can be concluded that there is a relationship between the workload of emergency department nurses and compliance with the implementation of new patient admission procedures. The conclusion in this study is that there is a relationship between the workload of emergency department nurses and compliance with the implementation of new patient admission procedures at RSU GMIM Pancaran Kasih, Manado City. Suggestions to hospitals can pay more attention to the workload they experience so as to provide good service to patients.